APLIKASI MOBILE COMMERCE (M-COMMERCE) BERBASIS ANDROID HYBRID - Sandro Alfeno; Wury Intan Tiana (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2018)
The number of uses of the Android operating system makes developers compete in making Android-based applications. One of them is in business, making a sales system that can run on Android-based smartphones is very popular with most people because it can facilitate buying and selling transactions. Based on the results of the research, the sales system at PT Gemanusa Sentra Teknologi still has some shortcomings. To solve this problem, a Mobile Commerce (M-Commerce) application is created by using the REST API as a communication method between Client and Server. With this application, it will be easier for users to make buying and selling transactions because they can be used anywhere and anytime.